Short Communication: Effect of urban greening and land use on air pollution in Chelyabinsk, Russia - TATYANA G. KRUPNOVA; OLGA V. RAKOVA; ANNA L. PLAKSINA; SVETLANA V. GAVRILKINA; EVGENY O. BARANOV; ANTON D. ABRAMYAN (Society for Indonesian Biodiversity, 2020)
Abstract. Krupnova TG, Rakova OV, Plaksina AL, Gavrilkina SV, Baranov EO, Abramyan AD. 2020. Effect of urban greening and land use on air pollution in Chelyabinsk, Russia. Biodiversitas 21: 2716-2720. Chelyabinsk is a major industrial Russian city that faces diverse environmental issues, the most important of which is air emissions. The primary sources of air pollution in Chelyabinsk are industry (concrete product plants, ferrous and nonferrous metallurgy such as zinc production plants, and pulp production), thermal power stations, and transport. People have known that trees can help to reduce air pollutants for a long time. We studied 8 zones within a radius of one kilometer from state air pollution monitoring stations. Eight land-use types such as industrial category, residential category, natural and semi-natural broadleaved vegetation, natural and semi-natural coniferous vegetation, broadleaved forest, coniferous forest, artificial broadleaved vegetation, and artificial coniferous vegetation, were obtained. The response of air pollution to land-use and urban greening was analyzed. Analysis results showed that there was no correlation between industrial and residential categories of land-using and concentrations of the most dangerous air pollutants in Chelyabinsk (formaldehyde, hydrogen fluoride, and nitrogen dioxide). The dominant factor affecting urban air quality was urban greening.